1991
DOI: 10.1007/bf00003585
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of plantlets fromEnteromorpha (Ulvales, Chlorophyta) protoplasts in axenic culture

Abstract: High yields of protoplasts have been obtained from vegetative thalli of three species of Enteromorpha by enzymatic degradation of the cell wall. Several commercial and crude enzymes prepared from the digestive system and hepatopancrease of abalone and top-shell were tested at different concentrations and combinations to evaluate the yield. Commercial enzymes in combination with either abalone or top-shell crude enzymes, consistently produced a high yield of protoplasts from all three species. High regeneration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Unlike higher plants and their protoplasts, all cells and protoplasts of seaweeds, with their simple morphological and anatomical thallus structure, regenerate and differentiate directly into a complete thallus, in many cases even without the addition of any growth regulators to the culture medium. Maximum regeneration rate (>90%) of protoplasts in Ulva and Enteromorpha was observed in cultures grown at 20°C and 25°C, while at 30°C there was a lack of differentiation of fronds from the rhizoidal system which grew prominently (Reddy and Fujita 1991). The continued presence of osmoticum >0.4 M in culture medium hampered cell division and further growth in both Ulva and Porphyra .…”
Section: Protoplast Isolation Culture and Regenerationmentioning
confidence: 94%
“…Unlike higher plants and their protoplasts, all cells and protoplasts of seaweeds, with their simple morphological and anatomical thallus structure, regenerate and differentiate directly into a complete thallus, in many cases even without the addition of any growth regulators to the culture medium. Maximum regeneration rate (>90%) of protoplasts in Ulva and Enteromorpha was observed in cultures grown at 20°C and 25°C, while at 30°C there was a lack of differentiation of fronds from the rhizoidal system which grew prominently (Reddy and Fujita 1991). The continued presence of osmoticum >0.4 M in culture medium hampered cell division and further growth in both Ulva and Porphyra .…”
Section: Protoplast Isolation Culture and Regenerationmentioning
confidence: 94%
“…Protoplasts of U. fasciata were isolated enzymatically with 4% cellulase Onozuka R‐10 and 2% Macerozyme R‐10 (Yakult Honsha Co. Ltd., Tokyo, Japan) in 10 mL of 1.2 M sorbitol solution. All isolation procedures were carried out in the dark (Marchant and Fowke 1977, Cheney et al 1986, Reddy and Fujita 1991) to promote the sinking of isolated protoplasts (Liu et al 1992) at 24° C. The yield of freshly isolated protoplasts was counted with a hemacytometer (Bright‐Line, improved Neubauer, 0.1 mm deep) under a light microscope (Zeiss, Axioskop; Zeiss, Jena, Germany). The experiments in this study were performed at least three times.…”
Section: Methodsmentioning
confidence: 99%
“…Protoplasts from U. pertusa and E. prolifera were prepared separately according to the previous methods (Reddy etal., 1989;Reddy & Fujita, 1991). After isolation, protoplasts were recovered from the debris by filtration through 30 tim mesh and centrifuged.…”
Section: Protoplast Isolationmentioning
confidence: 99%
“…Fujita and Saito (1990) also recently demonstrated intraspecific protoplast fusion of Porphyra by electrofusion method. In earlier studies, we have reported the development of suitable techniques for protoplast preparation, culture and regeneration of Ulva and Enteromorpha (Reddy & Fujita, 1991) in axenic culture. In this study we report the intergeneric electrofusion and regeneration of fusion products of protoplasts from Ulva pertusa with Enteromorpha prolifera, including:…”
Section: Introductionmentioning
confidence: 99%